IMPLEMENTATION OF LESSON PLAN CIVICS SUBJECT IN JUNIOR AND SENIOR HIGH SCHOOL TRENGGALEK REGENCY - Ramadhani, Syafira (Universitas Islam Balitar, 2025)
This study aims to implement the Pancasila and Citizenship Education learning implementation plan at the Junior High School and Senior High School levels in Trenggalek Regency. The learning implementation plan is an important instrument in the learning process designed to achieve national education goals, especially in shaping the character and national insight of students. This study uses a qualitative approach with a descriptive method. Data were obtained through observation, in-depth interviews, and document studies of Pancasila and Citizenship Education teachers in several Junior High Schools and Senior High Schools in Trenggalek Regency.The results of the study indicate that most teachers have implemented the learning implementation plan in accordance with the guidelines set by the Ministry of Education, Culture, Research, and Technology. However, there are several obstacles such as limited time in implementing learning, lack of supporting facilities, and variations in the level of teacher understanding of the preparation of learning implementation plans based on the Merdeka Curriculum. In addition, the adaptation of project-based learning and the integration of Pancasila values ​​into teaching and learning activities are challenges in themselves.This study recommends ongoing training for teachers to improve their competence in preparing and implementing innovative and contextual learning implementation plans. In addition, support from schools and local governments is needed to create a conducive learning environment. With the implementation of an effective learning implementation plan, it is hoped that Pancasila and Citizenship Education learning can be more optimal in forming students who are characterful, critical, and nationalistic.